2016
DOI: 10.19150/me.6422
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the fire hazards of mine materials using a radiant panel

Abstract: The objective of this study was to develop a laboratory-scale method to rank the ignition and fire hazards of commonly used underground mine materials and to eliminate the need for the expensive large-scale tests that are currently being used. A radiant-panel apparatus was used to determine the materials’ relevant thermal characteristics: time to ignition, critical heat flux for ignition, heat of gasification, and mass-loss rate. Three thermal parameters, TRP, TP1 and TP4, were derived from the data, then deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…The experimental configurations and methodologies used for the radiant panel experiments and the smoke chamber experiments, along with detailed results, are presented by Harteis et al and Litton et al, respectively [6,9]. These experiments and the parameters derived from the radiant panel and smoke chamber experiments will be discussed and summarized in the following sections and then used to assess the overall fire hazard.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The experimental configurations and methodologies used for the radiant panel experiments and the smoke chamber experiments, along with detailed results, are presented by Harteis et al and Litton et al, respectively [6,9]. These experiments and the parameters derived from the radiant panel and smoke chamber experiments will be discussed and summarized in the following sections and then used to assess the overall fire hazard.…”
Section: Methodsmentioning
confidence: 99%
“…More details of this research can be found in the paper by Harteis et al [9]. These parameters are listed in Table 1 for the materials tested in this portion of the research.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation